When does lexical availability influence phonology? Evidence from Jargon reading and repetition. Issue 4 (5th May 2020) - Pilkington, Emma; Sage, Karen; Saddy, Douglas; Robson, Holly
ABSTRACT: Jargon aphasia is a language disorder characterised by phonological and nonword error. Errors are thought to arise when target segments are insufficiently activated, allowing non-target or recently used phonology to intrude. Words which are more frequent and familiar reside with greater degrees of activation and therefore should be less susceptible to error. The current study tested this hypothesis in a group of 10 people with Jargon aphasia using single word repetition and reading aloud. Each task had two lexicality conditions, one high and one low lexical availability word set. Measures of nonword quantity, phonological accuracy and perseveration were used in group and case series analyses. Results demonstrated that fewer nonwords were produced when lexical availability was greater. However, lexicality effects on phonological accuracy and perseveration were only observed in repetition in a sub-group of moderately impaired individuals, demonstrating that lexical information does not consistently influence phonological processing in Jargon aphasia.